If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 2) + -4(3 + -1x) = 2x + -6 Reorder the terms: 3(2 + x) + -4(3 + -1x) = 2x + -6 (2 * 3 + x * 3) + -4(3 + -1x) = 2x + -6 (6 + 3x) + -4(3 + -1x) = 2x + -6 6 + 3x + (3 * -4 + -1x * -4) = 2x + -6 6 + 3x + (-12 + 4x) = 2x + -6 Reorder the terms: 6 + -12 + 3x + 4x = 2x + -6 Combine like terms: 6 + -12 = -6 -6 + 3x + 4x = 2x + -6 Combine like terms: 3x + 4x = 7x -6 + 7x = 2x + -6 Reorder the terms: -6 + 7x = -6 + 2x Add '6' to each side of the equation. -6 + 6 + 7x = -6 + 6 + 2x Combine like terms: -6 + 6 = 0 0 + 7x = -6 + 6 + 2x 7x = -6 + 6 + 2x Combine like terms: -6 + 6 = 0 7x = 0 + 2x 7x = 2x Solving 7x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7x + -2x = 2x + -2x Combine like terms: 7x + -2x = 5x 5x = 2x + -2x Combine like terms: 2x + -2x = 0 5x = 0 Divide each side by '5'. x = 0 Simplifying x = 0
| n+2-2n=-1 | | c=5b+200forb | | b^2+2b-3= | | 1ox+7=207 | | -4(c-24)=-4c-24 | | 8x+6+7x-3=108 | | -2f+7f=29 | | 2(4x+3)-2=x+20 | | 9x+5=8x-6 | | -27=-7(3b-8) | | 2h-4x=13 | | M+4m=-15 | | 2x^2+x=180 | | E=8b+12nforb | | -23=2n-7n | | 4x-2h=13 | | -18x-24=-9x+3 | | 3(5+7p)=120 | | (6x^3-4)+(2x^3+9)= | | -2(9d-8)=34+6d | | -b-4+3b=3+b | | X+17=3x-23 | | 5x+2y^3+xy^2=0 | | 8x+11-6x=5(x+7) | | 5x+2x-8=13 | | 4y-13=23# | | 48t-33=51t-69 | | -3(10)+9=-21 | | -98=2(-7+7x) | | 8(6-7y)=26 | | -3-6n=-3(1+4n)+6n | | 4x+24=8x-12 |